Effects of Folic Acid on Nursery Pig Growth Performance and Serum Homocysteine - Larissa L. Becker; Jordan T. Gebhardt; Mike D. Tokach; Robert D. Goodband; Joel M. DeRouchey; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 350 barrows (DNA 200 × 400; initially 13.2 ± 0.12 lb) were used in a 38-d growth study to determine the effects of folic acid on nursery pig growth performance and blood measurements. Pigs were weaned at approximately 21 d of age and randomly allotted to 1 of 5 dietary treatments in a completely randomized design. A total of 70 pens were used with 5 pigs per pen and 14 replications per treatment. Dietary treatments were corn-soybean meal-based and consisted of increasing folic acid: 0, 5, 10, 20, or 40 ppm. Treatment diets were fed in three phases from d 0 to 10 (phase 1), d 10 to 23 (phase 2), and d 23 to 38 (phase 3) after weaning. For phase 1 (d 0 to 10), there were no differences (P>0.10) in BW, ADG, or ADFI across treatments. However, increasing folic acid resulted in poorer F/G (linear,P= 0.032). For phase 2 (d 10 to 23), there was a marginally significant response in BW, ADG, and ADFI where performance was reduced as folic acid increased with the poorest performance observed when pigs were fed 20 ppm (quadratic,P≤ 0.079). No treatment differences (P>0.10) were observed for F/G. For phase 3 (d 23 to 38) and overall (d 0 to 38), there was a significant response in final BW, ADG, ADFI, and F/G where performance was reduced with increasing folic acid with the poorest performance observed when pigs were fed 20 ppm (quadratic,P≤ 0.049). On days 10 and 23, 70 pigs were bled to determine serum homocysteine concentration, and a marginally significant treatment × day interaction was observed (linear folic acid,P= 0.069). An increase (linear,P= 0.037) in homocysteine concentrations was observed as folic acid increased from 0 to 40 ppm in the diet on d 10; however, no differences were observed across increasing folic acid treatments on d 23 (P= 0.450). Pigs had increased (P<0.001) homocysteine concentrations on d 10 compared to d 23. In summary, the addition of folic acid resulted in reduced growth performance with the greatest impact being observed when pigs were fed 20 ppm.
Keywords: folic acid; nursery pig; growth; homocysteine